COMMUNICATION STRATEGIES APPLIED BY HIGH LEVEL OF EFL STUDENTS IN EXTENSIVE SPEAKING CLASS - Khoiriyah, Khoiriyah (Universitas Nusantara PGRI Kediri, 2015)
Communication is interaction between one person and others through verbal and nonverbal communication. Being able to communicate effectively is the optimal goal of all language learners; therefore, despite difficulties they face and restrictions they have while expressing themselves, they rely on employing diverse communication strategies (CSs). This case study was set to describe the types of communication strategies applied by high level of EFL students in extensive speaking class and to identify types of communication strategies are frequently used by high level of EFL students in extensive speaking class. Third grade of English department at Nusantara PGRI Kediri University students of EFL were assigned to participate in the present study. The participants' speaking performances were analyzed qualitatively using Dornyei's (1995) taxonomy of CSs. The results of the study revealed that the context of communication plays a significant role in the use of communication strategies. The high level students applied seven communication strategies out of the twelve types of communication strategies such as: message abandonment, topic avoidance, use of non-linguistic signal, literal translation, code switching, appeal for help, and stalling for time gaining. The most frequently used were time gaining and non-linguistic signal strategies.